Impact of creeping vegetable cover crops on weed flora composition during the early growth of Hevea (Natural Rubber) samplings in a tropical rain forest zone - Okore I K; Akpobome F A (Journal of the Rubber Research Institute of Sri Lanka, 2009)
Weed management is amongst the most expensive agronomic practice in immature rubber plantation. Field experiment was conducted during the rainy seasons of 2004 and 2005 at the Rubber Research Institute of Nigeria. The purpose was to assess the impact of some creeping economic vegetable crops (vegetable cowpea-Vigna unguiculata L. Walp. ssp sesquipedallis, Egusi melon-Cucumeropsis manni Naaud, Fluted pumpkin-Telfairia occidentalis Hook. F and Pumpkin-Cucumbita pepo) compared to the conventional cover crop (Centrosema pubescens) on weed flora composition when grown with rubber saplings. The experiment was laid out in a randomized complete block design with four replications. Weed flora comprising of 33 species under 17 plant families was observed across the field. Panicum maximum, Elusine indica, Brachiaria lata and other grass and sedge species like Talinum triangulare, Peporomia pellucida, Acalypha cillata and other broad leave weeds dominated in creeping vegetable crop plots, except the Telfairia plot which has weed flora closely similar to those of the conventional cover crop plots. The weed spectrum, density and dry matter weight were significantly lower in the Curcubita pepo and Cowpea plots compared to the conventional cover crop plots. The effect of the cover crops on the plant height and stem girth did not differ significantly within the first 12 months. Thus, it could be said that with the exception of the Telfairia occidentalis, the creeping vegetable crops could be importance for the control of noxious weed flora in immature rubber.
Keywords: Density; Growth performance; Intercrop; Species; Spectrum